Multisystemic therapy for rehabilitating children on proof of offence: concept, assumption, principles and intervention - Omar, Noralina; Abu Bakar Ah, Siti Hajar; Mohd Yusoff, Jal Zabdi; Omar, Noralina (The Malaysian Journal of Social Administration, 2018)
This conceptual paper discusses the characteristics of an effective family-based rehabilitation program for children on proof of offence. The program was introduced to respond to the alarming increase in the number of children involved in crimes. Section 91 (b) of the Child Act 2001 gazetted that children are placed under the care of responsible family or guardian/relatives that are considered fit to perform the care. Also, under the Section of 93 (1) the Court for Children can supplement injunction order for full responsibility and active participation of the families in the rehabilitation of the child. The authors are of the opinion that it is necessary to explain the program as it can assist members of the public, in particular, practitioners (i.e., probation officer, counsellor, Child Protectors) who administering and conducting the program understand the meaning, principles, approach and techniques that underlie the implementation of the program.